Testing Inference in Inflated Beta Regressions under Model Misspecification - Souza, Tatiene C.; Pereira, Tarciana L.; Cribari-Neto, Francisco; Lima, Verônica M. C. (Communications in statistics. Simulation and computation, 2016)
We consider testing inference in inflated beta regressions subject to model misspecification. In particular, quasi-z tests based on sandwich covariance matrix estimators are described and their finite sample behavior is investigated via Monte Carlo simulations. The numerical evidence shows that quasi-z testing inference can be considerably more accurate than inference made through the usual z tests, especially when there is model misspecification. Interval estimation is also considered. We also present an empirical application that uses real (not simulated) data.